Determinants of Immune Response to Anti–SARS-CoV-2 mRNA Vaccines in Kidney Transplant Recipients: A Prospective Cohort Study. Issue 4 (6th January 2022) - Magicova, Maria; Zahradka, Ivan; Fialova, Martina; Neskudla, Tomas; Gurka, Jiri; Modos, Istvan; Hojny, Michal; Raska, Petr; Smejkal, Petr; Striz, Ilja; Viklicky, Ondrej
Abstract : Background: Immune response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination has been recently shown to be impaired in kidney transplant recipients (KTRs), but the underlying factors affecting vaccine effectiveness need to be further elucidated. Methods: In this prospective cohort study, antibodies against S1 and S2 subunits of SARS-CoV-2 were evaluated using an immunochemiluminescent assay (cutoff 9.5 AU/mL, sensitivity 91.2%, and specificity 90.2%) in 736 KTRs, who were previously either naive or infected with SARS-CoV-2 and vaccinated before or after transplantation. Cellular response was analyzed in a subset of patients using an interferon gamma release assay (cutoff 0.15 IU/mL, sensitivity 92%, and specificity 100%). Results: Seroconversion was significantly more impaired in SARS-CoV-2–naive KTRs than in those previously infected (40.1% versus 97.1%; P < 0.001). Mycophenolate use (odds ratio, 0.15; 95% confidence interval, 0.09-0.24; P < 0.001) and depleting therapy in the past year (odds ratio, 0.19; 95% confidence interval, 0.05-0.8; P = 0.023) were found to be among independent factors associated with impaired humoral response. Similarly, the interferon gamma release assay tested in 50 KTRs (cutoff 0.15 IU/mL, sensitivity 92%, specificity 100%) showed that specific T-cell responses against spike protein epitopes are impaired in SARS-CoV-2–naive KTRs, as compared to previously infected KTRs (9.4% versus 90%, P < 0.001). All 35 KTRs vaccinated on the waiting list before transplantation exhibited sustained seroconversion persisting after transplantation. Conclusions: Survivors of coronavirus disease 2019 and those vaccinated while on the waiting list exhibited a marked immune response to mRNA vaccines, contrary to poor response in naive KTRs vaccinated after transplantation (NCT04832841). Abstract :